Bidirectional synaptic transmission in Necturus taste buds - Ewald, DA (J Neurosci, 1994)
Pairs of taste cells were impaled with intracellular recording microelectrodes in intact taste buds in slices of Necturus lingual epithelium. Applying short pulses of 140 mM KCl or 200 mM CaCl2 solutions to the apical pore elicited receptor potentials in taste receptor cells. Chemostimulation of receptor cells elicited postsynaptic responses in basal cells in the taste bud. Postsynaptic responses in basal cells had a threshold for activation and did not saturate with increasing doses of chemical stimulus applied to the receptor cells. We directly depolarized individual receptor cells and tested whether this would evoke postsynaptic responses in basal cells. Depolarizing receptor cells to approximately 0 mV evoked small depolarizing responses in basal cells in 16% of the experiments. The properties of these responses were consistent with their being mediated by a chemical synapse. A comparison of the responses in basal cells evoked by depolarizing single receptor cells, with responses evoked by stimulating the entire receptor cell population with KCl suggests that there is extensive synaptic convergence from receptor cells onto each basal cell. We also tested whether electrical excitation of basal cells would elicit (retrograde) synaptic responses in receptor cells. Single depolarizing pulses (up to 1 sec duration) applied to basal cells through the intracellular recording microelectrode never evoked synaptic responses in receptor cells. However, when repetitive electrical stimuli were applied to basal cells (four to six 1 sec depolarizations to approximately 0 mV every 12 sec) we observed prolonged effects on receptor cells in 11 of 23 experiments. These effects included an increase in the amplitude of receptor potentials elicited by KCI (mean +/- SD = +19 +/- 5%), an increase in membrane input resistance of receptor cells (+27 +/- 11%), and a hyperpolarization of receptor cells (3–10 mV). In control experiments, repetitive stimulation of one receptor cell never elicited such effects in another receptor cell. We investigated the possibility that serotonin (5-HT), released from basal cells, mediated the above modulatory effects on receptor cells. Bath-applied 5-HT (100 microM) mimicked the effects produced by repetitive basal cell stimulation (KCI responses increased by 23 +/- 12%; input resistance increased by 24 +/- 11%; hyperpolarization of 5–15 mV; N = 14). We conclude that basal cells release 5-HT onto adjacent taste receptor cells and that this enhances the electrotonic propagation of receptor potentials from the apical (chemosensitive) tip to the basal (synaptic) processes of receptor cells. The net effect is that activation of basal cells effectively increases the chemosensitivity of taste receptor cells.